IS PERIODONTITIS A HARBINGER OF RHEUMATOID ARTHRITIS? - A. V. Gordeev; E. A. Galushko; N. M. Savushkina; A. M. Lila (Научно-практическая ревматология)
Increasing attention in rheumatology is currently paid to the detection of diseases in the earliest (preclinical) stages, which can contribute to a more favorable response to therapy. To this end, various clinical, laboratory (and primarily immunological) and instrumental parameters are studied as a possible harbinger of rheumatic diseases (RDs). Periodontal diseases (PD) may be possible predictors for the development of RDs, and particularly rheumatoid arthritis (RA). This review considers the relationship between the development of periodontitis and RA and discusses the participation of individual microorganisms in the pathogenesis of PD and RA. The cell-mediated mechanisms that cause the chronic inflammatory process and lead to bone resorption are discussed. The role of PD and P. gingivalis in the processes of impaired autoantigen citrullination is described. Whether biological agents may be used to treat RDs accompanied by severe PD is considered.